A produção escrita de crônicas em sala de aula do 9º ano do ensino fundamental - Costa, Fernanda Maria da Serra (2018)
The present work deals with the development of written competence of students of the 9th grade of elementary school, through a didactic sequence applied to the genre chronicles, aiming to provide advances in the writing process. For the theoretical contribution, genre approaches are preferred from the perspective of Bakhtin (2011), Bazerman (2009), Bazerman e Miller (2011) e Marcuschi (2015). The methodology involves an action research, according to Gil's (2008) elucidations. The procedure is based on the application of a didactic sequence, inspired by contributions of Dolz, Noverraz and Schneuwly ([2004] 2013), Swiderski and Costa-Hübes (2009), Lopes-Rossi (2011), Vieira (2005) e Serafini (2003), with a view to learning text production of the genre chronicle under the point of view of writing as a process. Through the activities of reading and writing of chronicles, it is noticed that the students have reflected on the procedures of writer, they have sensitized more their look at the quotidian and have extended the knowledge of their linguistic competence. It is believed that providing learning situations by presenting them not as a burden, but with the grace - despite all the necessary pedagogical investment - that writing can have, thus ensuring that students finish elementary school having the opportunity to prepare texts according to their right to be proficient in their mother language.